Data on Costs of Advisory Services in Mozambique and Tanzania - International Food Policy Research Institute; The World Bank; Mama's Hope Organization for Legal Assistance; Government of Mozambique (International Food Policy Research Institute, 2019)
The data provide details on the costs of two interventions on gendered community-based advisory services. One intervention took place in Mozambique, focusing on agricultural extension on sustainable land management (SLM) practices, the other in Tanzania, which provided paralegal aid through community workers advising farmers on land rights. For each of the two programs, detailed data were collected on costs incurred by the implementation agency for the period of the project—May 2013 through July 2014 for Tanzania and 2010 to 2013 for Mozambique. The data were recorded monthly in Tanzania, and in an even more detailed manner in Mozambique, by time of acquisition or expenditure of each item or activity. The costs were all based on actual expenditures, and not on budgeted figures. In the case of Tanzania, cost data were submitted by implementing agency, Mama's Hope Organization for Legal Assistance (MHOLA), to the research team every three months, giving opportunity to obtain timely clarification and ask for corrections in cases of incorrect entries, while in the case of the Mozambique program, data were obtained from the project after project completion. All data were available highly disaggregated by labour cost (including type of labour and type of compensation such as allowances, salary, stipends, and so forth), transport costs (for example, fuel), capital outlays (such as purchase of motorcycles and furniture), office operational costs, workshop and training expenses, and other categories. In the Tanzania project, expenditures were recorded at the district level of the two intervention districts, such that the intervention cost can be measured separately for each district. Some types of costs that were more centralized and were not direct field outlays were assigned to the central project office in Bukoba. The spatial details of costs are richer and more complex in the Mozambique program. Costs at the lowest (community) level center around goods and services directly provided to contact farmers. The most significant costs at the administrative post level are those associated directly with extension officers, of which two are deployed in each post. At the district level, the program put in place a district facilitator and an environmental specialist to attend to various aspects of the project. Central costs include all the expenses of compensation of non-field-project staff for them to design and conduct the program, their travel costs to get to the field sites, capital outlays such as for vehicles, and various operational expenditures.